Annealing Treatment on Homogenous n-TiO2/ZnO Bilayer Thin Film Deposition as Window Layer for p-Cu2O-Based Heterostructure Thin Film - Mohamad Arifin, Nurliyana Mohamad; Mohamad, Fariza; Hussin, Rosniza; Mohd Ismai, Anis Zafirah; Ahmad Ramli, Shazleen; Ahmad, Norazlina; Muhd Nor, Nik Hisyamudin; Sahdan, Mohd Zainizan; Mohammad Zain, Mohd Zamzuri; Izaki, Masanobu (Mdpi, 2023)
Metal oxide semiconductor material has great potential to act as window layer in p–n heterojunction solar cell thin film owing to low production cost and significant properties in photovoltaic mechanism. In this work, n-TiO2/ZnO bilayer thin film was effectively constructed by means of sol-gel spin coating technique in an effort to diminish the electron-hole recombination rate from single-layered thin film. Annealing time is one of the important parameters in the fabrication process and was varied to study the impact of annealing treatment towards the thin film characteristics as window layer. It was found that the optimum parameter for the n-TiO2/ZnO bilayer was 500 ◦C with an annealing time of 2 h. High crystallinity of the n-(101)-TiO2/(002)-ZnO bilayer thin film was obtained, which consists of anatase and a hexagonal wurtzite structure, respectively. Orientation of (002)-ZnO is essential for deposition with the (111) Cu2O-absorbing layer due to a low different lattice mismatch between these two interfaces. The homogenous morphology of n-TiO2/ZnO bilayer was observed with a compact and dense layer. The improvement of transmittance has also been achieved in a range of 60%–80%, which indicated that the incident light can penetrate throughout the thin film directly. In addition, a p-Cu2O absorbing layer was successfully fabricated on top of n-TiO2/ZnO bilayer thin film to form a p-n junction in order to visualize significant electrical rectification properties. The existence of p-Cu2O was confirmed by a (111)-peak orientation and triangular shape in structural and morphological properties, respectively